Принципи використання інформаційних технологій правоохоронними органами - Калюжний, Дмитро (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The article reveals the replacement of the principles of the use of information and communication technologies in law enforcement. It is stated that information technologies are defined as methods and methods that use computer software and hardware, in addition to aggregate information processes and operations to achieve the target goal. In turn, the term “information and communication technologies” means the result of intellectual activity, the totality of systematized scientific knowledge, technical, organizational and other decisions about translocation and the sequence of operations for collecting, processing, accumulating and obtaining information products, providing information services. The principles of using ICT by the law enforcement system can be divided into two groups: fundamental and methodological. Their dissolution is accompanied by the importance of legality, the security of the country’s defense, socio-political stability and the development of democratic ambushes in the governed state.